Carpal tunnel syndrome in cardiac amyloidosis: implications for early diagnosis and prognostic role across the spectrum of aetiologies. (23rd January 2020) - Milandri, Agnese; Farioli, Andrea; Gagliardi, Christian; Longhi, Simone; Salvi, Fabrizio; Curti, Stefania; Foffi, Serena; Caponetti, Angelo Giuseppe; Lorenzini, Massimiliano; Ferlini, Alessandra; Rimessi, Paola; Mattioli, Stefano; et al.
Abstract: Aims: We aimed to assess carpal tunnel syndrome (CTS) prevalence in transthyretin (TTR)‐related and light‐chain amyloidosis (AL), comparing it to the general population, adjusted for age and gender. In TTR‐related amyloidosis (ATTR) we investigated (i) CTS prevalence in relation to genotype, cardiac amyloidosis (CA), age and gender; (ii) CTS role as an incremental risk factor for CA; (iii) temporal relationship between CTS and CA; and (iv) CTS prognostic role. Methods and results: Data from 538 subjects (166 hereditary ATTR, 107 wild‐type ATTR, 196 AL amyloidosis, and 69 TTR mutation carriers; 64% male, median age 62.4 years), evaluated at our centre (Bologna, Italy), were analysed and compared to a published cohort of 14.9 million people, in which incidence rates of CTS had been estimated. CTS prevalence was highest in ATTR patients with CA (20.3% vs. 4.1% in the general population), while it was comparable to the general population when CA was absent and in AL patients. CTS standardized incidence rates were markedly elevated in ATTR males in the eighth decade of life (13.08 in hereditary ATTR, 15.5 in wild‐type ATTR). The risk of developing CA was greater in ATTR patients with CTS; the probability of having CTS was highest 5–9 years prior to CA diagnosis. CTS was an independent mortality risk factor in ATTR. Conclusions: Compared to general population the adjusted prevalence of CTS is higher among elderly men with ATTR; CTS is a prognostic marker in ATTR, independently of cardiac involvement, and precedes CA diagnosis by 5–9 years. The awareness of this association and time delay offers the possibility of an early pre‐clinical ATTR‐CA diagnosis.